2020
DOI: 10.3390/polym12081646
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Synthetic Polymers of Phenolic Compounds

Abstract: In recent years, developing potent antioxidants has been a very active area of research. In this context, phenolic compounds have been evaluated for their antioxidant activity. However, the use of phenolic compounds has also been limited by poor antioxidant activity in several in vivo studies. Polymeric phenols have received much attention owing to their potent antioxidant properties and increased stability in aqueous systems. To be truly effective in biological applications, it is important that these polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 153 publications
1
39
0
3
Order By: Relevance
“…When we treated H 2 DCFDA-stained amoebas with hydrogen peroxide, they exhibited a stronger fluorescence ( Supplementary Figure S3 ), suggesting that H 2 DCFDA can be used as an indicator for hydrogen peroxide. Using this approach, we found that pretreatment of amoebas with pyrocatechol, a ROS scavenger of hydrogen peroxide [ 67 , 68 ], reduced the hydrogen peroxide detected in viable amoebas, which is produced as a response to detoxify oxygen through diverse enzymes including NADPH:flavin oxidoreductase (Eh43), thioredoxin reductase (TrxR), NADPH-dependent oxidoreductases (NO1/2) or Fe-superoxide dismutase (FeSOD) [ 64 , 69 ]. The hydrogen peroxide reduction in trophozoites by pretreatment with pyrocatechol impacted the NETosis directly, since a smaller amount of DNA was detected in the extracellular medium.…”
Section: Discussionmentioning
confidence: 99%
“…When we treated H 2 DCFDA-stained amoebas with hydrogen peroxide, they exhibited a stronger fluorescence ( Supplementary Figure S3 ), suggesting that H 2 DCFDA can be used as an indicator for hydrogen peroxide. Using this approach, we found that pretreatment of amoebas with pyrocatechol, a ROS scavenger of hydrogen peroxide [ 67 , 68 ], reduced the hydrogen peroxide detected in viable amoebas, which is produced as a response to detoxify oxygen through diverse enzymes including NADPH:flavin oxidoreductase (Eh43), thioredoxin reductase (TrxR), NADPH-dependent oxidoreductases (NO1/2) or Fe-superoxide dismutase (FeSOD) [ 64 , 69 ]. The hydrogen peroxide reduction in trophozoites by pretreatment with pyrocatechol impacted the NETosis directly, since a smaller amount of DNA was detected in the extracellular medium.…”
Section: Discussionmentioning
confidence: 99%
“…Natural polyphenols are used as important base materials in enzymatic modification in order to obtain new chemical compounds with high antioxidant, antimutagenic, anticarcinogenic, antiviral, and anti-inflammatory properties [38][39][40][41][42]. Many biological and pharmacological properties of flavonoids and phytoalexins have been long known, but are still actively researched in the search for new biochemical activities.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of oxidation improves the stability of polymers to be effective in more applications [189]. The addition of antioxidant into films can change the structure of the film [190], where the reduction in the antioxidant impairs the resistance to degradation [191].…”
Section: Antioxidant Properties Of Wheat Based Filmmentioning
confidence: 99%